Rare Manifestation of Acute Blindness in Ocular Toxoplasmosis: A Case Report - Brimantyo, Dio; Arfijanto, M. Vitanata (Gaceta Médica de Caracas, 2023)
Introduction: Toxoplasmosis is one of the most common zoonoses worldwide. Clinical manifestations of ocular toxoplasmosis are highly specific. Atypical manifestations are not uncommon and are not always recognized as specific to ocular toxoplasmosis. Here, we present a rare manifestation of acute blindness in ocular toxoplasmosis in an immunocompetent patient.